1985
DOI: 10.3354/meps022153
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure of rocky intertidal communities response to wave action and implications for energy flow

Abstract: The influence of physical factors on the trophic structure of rocky intertidal communities in the Cape of Good Hope was investigated by examining species composition and biomass on shores subject to different conditions of substratum, sea temperature and wave exposure. Biomass of herbivores on shores with an unstable substratum was particularly high while the sessile filter-feeders and algae were impoverished, but actual rock type did not affect trophic structure. Sea temperature influenced species composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 18 publications
5
50
1
Order By: Relevance
“…Bustamente et al (1995) showed that densities of limpet populations on the west coast depended on the rate of kelp input. In this study we found that growth rates of mussels are affected by wave action (presumably as this dictates rates of food supply), and it has previously been shown that predator biomass in South Africa is correlated with filter-feeder biomass (McQuaid & Branch 1985, see also Menge 1992. Both filter-feeder and total animal biomass are significantly higher on exposed than sheltered shores (McQuaid & Branch 1985), and this may indicate the importance of energy subsidies into the system through the medium of wave action.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Bustamente et al (1995) showed that densities of limpet populations on the west coast depended on the rate of kelp input. In this study we found that growth rates of mussels are affected by wave action (presumably as this dictates rates of food supply), and it has previously been shown that predator biomass in South Africa is correlated with filter-feeder biomass (McQuaid & Branch 1985, see also Menge 1992. Both filter-feeder and total animal biomass are significantly higher on exposed than sheltered shores (McQuaid & Branch 1985), and this may indicate the importance of energy subsidies into the system through the medium of wave action.…”
Section: Discussionsupporting
confidence: 58%
“…In this study we found that growth rates of mussels are affected by wave action (presumably as this dictates rates of food supply), and it has previously been shown that predator biomass in South Africa is correlated with filter-feeder biomass (McQuaid & Branch 1985, see also Menge 1992. Both filter-feeder and total animal biomass are significantly higher on exposed than sheltered shores (McQuaid & Branch 1985), and this may indicate the importance of energy subsidies into the system through the medium of wave action. Higher growth rates on exposed shores also provide a mechanism which can explain the shift in dominance between filter-feeders on exposed shores and algae on sheltered shores recorded for the South African coast (McQuaid & Branch 1985).…”
Section: Discussionsupporting
confidence: 58%
“…Large waves also dislodge sessile organisms living on exposed rocky shores, leading to altered size distributions, redistribution of individuals or increased mortality (Alvarado & Castilla 1996, Hunt & Scheibling 2001. Wave exposure may affect the distribution and abundance of individual species, species interactions and entire rocky shore communities (McQuaid & Branch 1985, Menge & Branch 2001, Hammond & Griffiths 2004. Sessile ABSTRACT: Exposure to wave action is an important factor determining the distribution and abundance of marine species on rocky shores.…”
Section: Introductionmentioning
confidence: 99%
“…Menge (1978a,b) and Peterson (1979) found a negative relationship between wave exposure and the importance of consumers in structuring the intertidal in the northwestern Atlantic, but Robles (Robles & Robb 1993, Robles 1997 found the opposite when examining lobster predation in southern California. Negative correlations between wave exposure and consumer effect have been observed for tropical urchins (Foster 1987) and temperate urchins (Kawamata 1998), while no relationship was observed between exposure and herbivory in South African intertidal structure (McQuaid & Branch 1985).…”
Section: Introductionmentioning
confidence: 99%